2017
DOI: 10.1371/journal.pone.0185798
|View full text |Cite
|
Sign up to set email alerts
|

Childhood socioeconomic position and adult mental wellbeing: Evidence from four British birth cohort studies

Abstract: BackgroundThere is much evidence showing that childhood socioeconomic position is associated with physical health in adulthood; however existing evidence on how early life disadvantage is associated with adult mental wellbeing is inconsistent. This paper investigated whether childhood socioeconomic position (SEP) is associated with adult mental wellbeing and to what extent any association is explained by adult SEP using harmonised data from four British birth cohort studies.MethodsThe sample comprised 20,717 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…Additionally, life-courses are used to pinpoint where people are in their personal development process, drawing on characteristics that are typical for different phases of the life-course [1, 5, 6]. Because of their broad applicability, researchers interested in all age groups and in a variety of topics use life-courses to study, for example, the effects of childhood living conditions, the participation in further education at different ages, and pathways to financial well-being in retirement [711].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, life-courses are used to pinpoint where people are in their personal development process, drawing on characteristics that are typical for different phases of the life-course [1, 5, 6]. Because of their broad applicability, researchers interested in all age groups and in a variety of topics use life-courses to study, for example, the effects of childhood living conditions, the participation in further education at different ages, and pathways to financial well-being in retirement [711].…”
Section: Introductionmentioning
confidence: 99%
“…There is tentative evidence that another underlying difference between these two groups and between those with firmer retirement plans and plans to retire in the medium term may map onto socioeconomic differences. Socioeconomic factors can influence both decisions around retirement planning [10,33] and wellbeing [34]. While our prior typology was deliberately simplified and naïve, it is clear that the omission of socioeconomic circumstances leaves an incomplete picture.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the current COVID-19 pandemic has brought the issue of retirement from health and social services to greater prominence. Many frontline workers have returned from retirement to contribute to frontline responses to the pandemic, either through formal recruitment campaigns or voluntary schemes [34,35]. This underlines the skill and expertise that people are capable of bringing to services in the years beyond which they would have anticipated working.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis builds on the framework adopted by Wood et al 14 on the prediction of mental well-being as a single outcome15 across four UK birth cohort studies, which showed that childhood SES is directly and indirectly (through adult socio-economic pathways) linked to adult EWB. We expand on their approach by including four outcome measures, although for a single birth cohort.…”
Section: Introductionmentioning
confidence: 99%